2015
DOI: 10.1073/pnas.1504625112
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides regulate the mechanical hierarchy between subdomains of the nucleotide binding domain of the Hsp70 chaperone DnaK

Abstract: The regulation of protein function through ligand-induced conformational changes is crucial for many signal transduction processes. The binding of a ligand alters the delicate energy balance within the protein structure, eventually leading to such conformational changes. In this study, we elucidate the energetic and mechanical changes within the subdomains of the nucleotide binding domain (NBD) of the heat shock protein of 70 kDa (Hsp70) chaperone DnaK upon nucleotide binding. In an integrated approach using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(59 citation statements)
references
References 42 publications
4
54
0
Order By: Relevance
“…Several other conserved communities (L324-F356-V331) and (Q343-K270-M346) are shared by the DnaK structures forms and are responsible for structural stability of the subdomain IIA. According to single molecule optical tweezer experiments, nucleotide binding in DnaK is dependent on thermal stability of the subdomain IIA [127] . These studies also showed that stabilization and nucleotide-binding function of the lobe II in DnaK may be associated with structural preservation of residue cluster 330–345 in subdomain IIA.…”
Section: Resultsmentioning
confidence: 99%
“…Several other conserved communities (L324-F356-V331) and (Q343-K270-M346) are shared by the DnaK structures forms and are responsible for structural stability of the subdomain IIA. According to single molecule optical tweezer experiments, nucleotide binding in DnaK is dependent on thermal stability of the subdomain IIA [127] . These studies also showed that stabilization and nucleotide-binding function of the lobe II in DnaK may be associated with structural preservation of residue cluster 330–345 in subdomain IIA.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrolysis of ATP by the hsp70 NBD keeps the precursor SOD2 protein in an unfolded, import-competent state and increases dissociation of bound SOD2 from hsp70 at the outer mitochondrial membrane, thereby increasing the import and activity of SOD2 (14). Treatment of cultured PAECs with GERAMT-TAT markedly reduced SOD2 localization to the mitochondria at baseline and following ACh stimulation (Fig.…”
Section: ؉mentioning
confidence: 86%
“…The NBD has a deep cleft for binding ATP, while client proteins bind in a β-sandwich region of the SBD (Bertelsen et al, 2009). These two domains are allosterically linked, with nucleotide turnover in the NBD controlling the affinity of SBD-client interactions (Bauer et al, 2015; Clerico et al, 2015; Palleros et al, 1993; Zhuravleva and Gierasch, 2015). In the ATP-bound form, clients bind Hsp70s with fast-on, fast-off kinetics, while hydrolysis to the ADP-bound form stabilizes the SBD-client interaction by slowing the off-rate (Ha and McKay, 1995).…”
Section: Introductionmentioning
confidence: 99%